A 3D-printed Sn-doped calcium phosphate scaffold for bone tissue engineering - Liang, Hong; Fu, Gaosheng; Liu, Jinrui; Tang, Yueting; Wang, Yujue; Chen, Shan; Zhang, Yanjie; Zhang, Chen (Frontiers in Materials, 2022)
Recent developments in 3D printing technology have been applied in the field of tissue engineering to fabricate customized bone repair scaffolds. β-tricalcium phosphate (β-TCP) is a bioceramic material with excellent potential as a scaffold foundation. Doping metallic ions with β-TCP will significantly enhance the mechanical property and bone regeneration performance compared with pure β-TCP specimens. In this study, we propose a protocol for the fabrication of a Sn-doped β-TCP (Sn@TCP) scaffold using 3D printing technology, and the effect of Sn-doping on the physicochemical properties of the material and its in vitro bioactivity were investigated. Polyethylene glycol and polyvinyl alcohol were used as binder to construct Sn@TCP scaffold which have good biocompability and can break down into H2O and CO2 after scaffold sintering. The appearance of the scaffold constructed by 3D printing technology closely matched the computer design. The incorporation of Sn into β-TCP improved the compressive strength of the scaffold. Moreover, the Sn@TCP scaffold retained the inherently good biocompatibility of β-TCP and exhibited better osteoinduction capability than pure β-TCP scaffolds. Notably, the osteoinduction ability of Sn@TCP scaffolds were dependent on the Sn content. In conclusion, the 3D printing of Sn@TCP scaffolds with enhanced mechanical properties and osteoblast-inducing activity show great promise as scaffold materials in bone tissue engineering applications.